Efektivitas Penyaluran Dana Zakat Produktif Pada Program Satu Keluarga Satu Sarjana Dalam Pemberdayaan Mustahiq - Wandira, Novera; Abdullah, K.A. Bukhori; Cahaya, Peny (el Buhuth: Borneo Journal of Islamic Studies, 2023)
This study aims to analyze the planning and effectiveness of the distribution of productive zakat funds in the one-graduate one-family program in empowering mustahiq. In this study using a type of qualitative research with type descriptive explorative research aims to describe a situation phenomenon. Data collection was carried out by direct observation at BAZNAS South Sumatra Province, interviews with BAZNAS officials and recipients One Family One Graduate scholarship, and equipped with documentation. Data analysis using data collection, data reduction, data presentation, and withdrawal conclusion. The results of the study on the effectiveness of the distribution of productive zakat funds in the one-graduate one-family program in empowering mustahiq are: BAZNAS of South Sumatra Province improves the quality of human resources in the field of education through the One Family One Bachelor program by providing scholarships of IDR 2.500.000 to underprivileged students each semester to assist mustahiq in paying a single tuition fee. The distribution of productive zakat funds at BAZNAS of South Sumatra Province using the Allocation to Collection Ratio (ACR) shows a calculated result with a percentage of 83% and the results of interviews with the head of productive zakat, the coordinator of the One Family One Bachelor program and 15 scholarship recipients are effective.